THE USE OF CORRESPONDENCE ANALYSIS IN THE EVALUATION OF THE ROLE OF FIBROUS AND MEDICINAL PLANTS IN PLANT PRODUCTION IN FARMS - Sompolska-Rzechuła, Agnieszka; Spychalski, Grzegorz (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
The paper presents the usage of multidimensional correspondence analysis to estimation the role of fibre and medicinal plants in farms plant production in the context of the determinants influencing the choice of these plants for crop rotation scheme. The source of data were the survey questionnaires collected among the farmers running agricultural activity in the period 2011-2012 in the Wielkopolska region. The correspondence analysis enabled to indicate relations a selected categorical variable and such categories as age, sex, education, number of person per household, farm area and farm income in 2010 and 2011.